The Effect of Liming Time on Protein Content, Moisture, Calcium, Volume Expansion and Organoleptic Quality of Rambak - Aris Sri Widati; Mustakim Mustakim; Sri Indriana (Faculty of Animal Science Universitas Brawijaya, 2007)
The aim of the research was to find out effect of liming time on quality of rambak. Completely Randomized Design (CRD) was used to execute the research. Four treatments of liming time was carried out in three replications were 24, 48, 72 and 96 hours. The Result showed that liming time had highly significant effect (P<0,01) on protein content, moisture, calsium, volume expansion and organoleptic quality (crispness and taste) of rambak. The best result was liming time of 96 hours, the rambak was characterised by protein contentÂ 6,10%, moisture 0.11%, calcium 1.88%, volume expansion ratioÂ 372.12%, crispness 0.42 lbs/cm2. Sensory evaluation showed that organolepticaly panelist preferred the product giving score of crispness 5.38 and taste 6.89. Â Keywords : Liming time, Rambak quality